Near‐patient coagulation testing to predict bleeding after cardiac surgery: a cohort study. Issue 2 (25th July 2017) - Mumford, Andrew D.; Harris, Jessica; Plummer, Zoe; Lee, Kurtis; Verheyden, Veerle; Reeves, Barnaby C.; Rogers, Chris A.; Angelini, Gianni D.; Murphy, Gavin J.
Abstract: Essentials Near‐patient testing improves coagulopathy diagnosis in cardiac surgery patients with severe bleeding. We investigated how well pre‐emptive near‐patient testing predicted severe bleeding. Severe bleeding could be predicted using both near‐patient tests and patient clinical characteristics. Near‐patient test results gave little additional predictive value over clinical characteristics alone. Background: Coagulopathic bleeding is common after cardiac surgery and is associated with increased morbidity, mortality and healthcare costs. Implementation of blood management algorithms in which patients with severe bleeding undergo near‐patient coagulation testing results in less overall bleeding and transfusion. However, it is unknown whether there is additional value from pre‐emptive near‐patient testing to predict whether severe bleeding will occur. Objectives: To evaluate how well a comprehensive panel of 28 near‐patient platelet and viscoelastometry tests predict bleeding after cardiac surgery, compared to prediction using baseline clinical characteristics alone. Methods: Single‐center, prospective cohort study in adults undergoing a range of cardiac surgery procedures. The primary outcome was clinical concern about bleeding (CCB), a composite of high blood loss (chest drain volume >600 mL within 6 hours), re‐operation for bleeding or administration of a pro‐haemostatic treatment directed by clinician judgement. Results: In 1833 patients recruited between March 2010 and August 2012, the median number of abnormal near‐patient test results was 5/28 per patient (range 0‐18). CCB occurred in 449/1833 patients (24.5%). The c‐statistic for a predictive model for CCB using only baseline clinical characteristics ( baseline‐only model) was 0.72 (95% CI 0.69‐0.75). Addition of near‐patient test results to this model ( baseline‐plus‐test model) improved the prediction of CCB (c‐statistic 0.75 [0.72‐0.77]), but increased the number of correctly classified patients by only 18 (0.98%). Conclusions: Near‐patient coagulation testing predicts bleeding in cardiac surgery patients, but offers little improvement in prediction compared to baseline clinical characteristics alone. trial registration: ISRNCTN 20778544 (http://www.isrctn.com/ ).